The Possibility of Using Artificial Intelligence in Judicial Decision-Making: An Example of Passive SUBSTANTIVE Standing - Hudej, Jasna (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The chapter explores how artificial intelligence could be involved in the decision-making process regarding cancellation actions (Land Registry Act). The question is answered after first having analysed the nature of the procedure in which a cancellation action is decided, whereby the focus is put on one aspect of the action – passive substantive standing. Limited to the acquisition of property rights through legal transactions, the conditions on the passive side that must be fulfilled are examined. The chapter analyses the position of the direct acquirer, the position of the subsequent acquirer in consecutive dispositions of the immovable property, and the position of the subsequent acquirer in multiple dispositions of the immovable property. The author concludes that the human judge is irreplaceable in the litigation procedure, where a cancellation action is decided. However, greater potential for integrating artificial intelligence is seen in the land registry procedures associated with this litigation procedure.